History, Introduction, and Kinetics of Ion Exchange Materials. (10th October 2013) - Kumar, Sanjeev; Jain, Sapna
Abstract : During the last few decades, ion exchange materials have evolved from laboratory tool to industrial products with significant technical and commercial impact. The current paper briefly summarizes the history of the development of the ion exchange materials. The paper defines the ion exchange materials and their types. The paper signifies the kinetics involved in the ion exchange process with description of factors affecting the rate of ion exchange. The mechanism of ion exchange has also been delineated through schematic diagram, illustrating that there are two types of diffusion, film and particle controlled diffusion. A brief of mathematical approach for kinetics of ion exchange has also been incorporated.